Impact of preterm birth on maternal wellbeing and women’s perceptions of their baby - Henderson, J; Carson, C; Redshaw, M (BMJ Publishing Group, 2016)
Background: Approximately 15 million babies were born preterm worldwide in 2010 and In England in 2014 there were 52, 249 preterm births. Preterm babies are at increased risk of poor outcomes and this can put enormous strain on the family. Objective: This study aimed to test the hypothesis that giving birth preterm affects maternal health, mood and wellbeing, and alters women’s feelings and perceptions about their baby. Methods: Data collected in a population based survey of maternity care in England in 2014 were used. Women were randomly selected and asked about their pregnancy, birth and postnatal experience when their babies were about 3 months of age. Descriptive statistics were produced, and logistic regression used to estimate odds ratios, adjusted for key confounders. Main outcome measures: Women’s self-reported postnatal health, Edinburgh Postnatal Depression Scale, women’s perceptions of their baby. Results: 4578 women returned completed questionnaires. Of these, 42 (0.9%) had babies born before 32 weeks’ gestation and 243 (5.5%) at 32-36 weeks. Comparing the three gestational age groups, no statistically significant differences in rates of depressive symptoms measured on the Edinburgh Postnatal Depression Scale were found. However, using a health problems checklist, anxiety, fatigue and flash-backs were more common in mothers of preterm babies. Overall, mothers of preterm babies had less early contact with their baby, more postnatal health problems, substantially less positive feelings towards their baby, and made less use of the support options available. Conclusion: Women with preterm births are at increased risk of ill-health and negative feelings about their baby in the early months after birth. They make less use of postnatal services and support than other women and this may be an area where the use of specialist services would be appropriate.